Atrial fibrillation and subtype of atrial fibrillation in cardiac amyloidosis: clinical and echocardiographic features, impact on mortality. (3rd July 2019) - Sanchis, Kevin; Cariou, Eve; Colombat, Magali; Ribes, David; Huart, Antoine; Cintas, Pascal; Fournier, Pauline; Rollin, Anne; Carrié, Didier; Galinier, Michel; Maury, Philippe; Duparc, Alexandre; et al.
Abstract: Background: Atrial fibrillation (AF) commonly affects patients with cardiac amyloidosis (CA). Amyloid deposition within the left atrium may be responsible for the subtype of AF in either permanent or non-permanent form. The prognostic implications of AF and its clinical subtype according to the type of CA are still controversial in this population. This study sought to investigate the prevalence, incidence and prognostic implications of AF and the clinical subtype of AF (permanent or non-permanent) in patients with CA. Methods: Two hundred and thirty-eight patients with CA and full medical records were retrospectively enrolled in the study: About 115 (48%) with light chain (AL) amyloidosis and 123 (52%) with transthyretin amyloidosis (ATTR). Patient's medical records were reviewed to establish baseline prevalence, incidence and impact on all-cause and cardiovascular mortality during follow-up of AF. Results: One hundred and four (44%) patients had history of AF at the time of diagnosis: 62 (60%) permanent and 42 (40%) non-permanent. There were 30 (26%) and 74 (60%) patients with history of AF among patients with AL and ATTR (including 5 hereditary and 69 wild-type), respectively ( p <.0001). During the follow-up, 48 new patients developed AF (29, 12 and 7 among patients with AL, wild-type ATTR and hereditary ATTR). After adjustment for age, survival was similar in patients with or without history of AF (HR 0.87 (95% CI, 0.60 to 1.27; p = .467). AF had no impact on cardiovascular mortality. Among the 152 patients with history of AF included in the whole study, there were 75 (49%) patients with permanent AF. After adjustment for age, survival was similar in patients with permanent and non-permanent AF: HR 1.29 (95% CI, 0.84 to 1.99; p = .251). The results were the same among patients with AL or wild-type amyloidosis. Subtype of AF had no impact on cardiovascular mortality. Conclusions: AF is common in patients with CA. However, AF and clinical subtype of AF have no impact on all-cause mortality, whatever the type of amyloidosis.